7+2+5 is 143566

Exam 5+3+2=151012 9+2+4=183662 8+6+3=482466 then 7+2+5=?

Look at the answer, we are working towards 7+2+5, now look at the first term (5+3+2) and shuffle then to make

3+2+5. Thus, except for the first term we are almost there. However, we can also say

7+2+5 (Answer) = (3+4)+2+5. So the first term is only a 4 short.

The second term has a 4 but also a 9+2. However, 9+2 = (6+3) + 2. The third term has a 6+3 but then you also have a 8 extra.

So,

5+3+2 = 151012 plus

9+2+4=183662 minus

8+6+3=482466 equals

7+2+5 + (9+2) = 151012 + 183662 = 334674

but

7+2+5 + (9+2) minus 8+6+3=482466 equals 7+2+5+ (2- 8) = 334674 - 183662 = 151012 which equals the first term of 5+3+2.

So,

7+ (2-8) = 3

or 7 = -(2-8)+3 = -2 + 8 + 11= 8 + 9 = 8 + 6 + 3 = 482466 ....(a)

So, the first term is now 5+3+2 = 151012 = 7 + 3 = 151012.

So, 7 = 482466 minus 7 + 3 = 151012, makes 3 = -331454.

So we go again back to the first term and see that

5+3+2 = 151012 minus makes 3 = -331454 equals

5+2 = [5 + 3 + 2] - 3 = 151012 - (-331454) = 482466 = 7 = 8+6+3 (previously proven, which confirms it. - See (a))

So, 7+2+5 = 7 + 7 = 482466 + 482466 = 964932

(In all honesty, I have a feeling I made a mistake somewhere, but I can't seem to find it now.)

My friend Deon found this as a very tricky problem and spent day and night trying to figure it out.

Look at the answer, we are working towards 7+2+5, now look at the first term (5+3+2) and shuffle then to make

3+2+5. Thus, except for the first term we are almost there. However, we can also say

7+2+5 (Answer) = (3+4)+2+5. So the first term is only a 4 short.

The second term has a 4 but also a 9+2. However, 9+2 = (6+3) + 2. The third term has a 6+3 but then you also have a 8 extra.

So,

5+3+2 = 151012 plus

9+2+4=183662 minus

8+6+3=482466 equals

7+2+5 + (9+2) = 151012 + 183662 = 334674

but

7+2+5 + (9+2) minus 8+6+3=482466 equals 7+2+5+ (2- 8) = 334674 - 183662 = 151012 which equals the first term of 5+3+2.

So,

7+ (2-8) = 3

or 7 = -(2-8)+3 = -2 + 8 + 11= 8 + 9 = 8 + 6 + 3 = 482466 ....(a)

So, the first term is now 5+3+2 = 151012 = 7 + 3 = 151012.

So, 7 = 482466 minus 7 + 3 = 151012, makes 3 = -331454.

So we go again back to the first term and see that

5+3+2 = 151012 minus makes 3 = -331454 equals

5+2 = [5 + 3 + 2] - 3 = 151012 - (-331454) = 482466 = 7 = 8+6+3 (previously proven, which confirms it. - See (a))

So, 7+2+5 = 7 + 7 = 482466 + 482466 = 964932

(In all honesty, I have a feeling I made a mistake somewhere, but I can't seem to find it now.)

My friend Deon found this as a very tricky problem and spent day and night trying to figure it out.